Challenges and strategies for establishing inclusive school in Indonesia: Aligning Islamic values with inclusive education principles - Luqmanul Hakim Muttaqin; Muhammad Haekal; Ibrahim Ibrahim; Ratna Tri Utami (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The global movement towards inclusive education has gained momentum in recent years, aiming to provide equitable education for all students, regardless of their abilities. Indonesia, in response to this transformative movement, has ratified an inclusive education policy, aiming to provide educational opportunities to students with disabilities within regular classroom settings. However, translating policy into practice poses significant challenges, with deeply entrenched medical model perspectives influencing public perceptions of individuals with disabilities.This article delves into the necessity of fostering a comprehensive understanding of and valuing diversity to support the establishment of an inclusive school environment in Indonesia. It explores the essential shift from the medical to the social model in understanding students with disabilities and highlights the significant role of beliefs and attitudes in shaping the implementation of inclusive education. Furthermore, it examines the alignment of Islamic values, particularly the "Fikih Difabel", with the principles of inclusive education.The article emphasizes the pivotal role of creating an inclusive culture within schools, guided by the Index for Inclusion, to develop sustainable inclusive practices. Strategies to overcome challenges in promoting acceptance and inclusivity among stakeholders, including educators, parents, and students, are proposed, such as education and awareness, engaging religious scholars, collaboration and partnership, cultivating an inclusive school culture, parent and community involvement, monitoring and evaluation, and advocacy for policy reform.By aligning inclusive education principles with Islamic values, specifically through the "Fikih Difabel," Muhammadiyah can lead by example in fostering inclusive school environments within its institutions. These efforts can positively impact the lives of students with disabilities and promote a sense of unity and empathy among all students, contributing to a truly inclusive society in Indonesia.